Penerapan Algoritma Untuk Menghitung Nilai Ujian Akhir Semester (UAS) di Perguruan Tinggi - Tobe, Nilam S.M; Missa, Vebrianti T; Teku, Maria M.B; Bupu, Maria A.; Lian, Yohanes P. (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to develop and implement an algorithm that can calculate the minimum Final Semester Examination (UAS) score required to pass a course. In the higher education system, evaluation of student academic performance is carried out through various assessment components such as assignments, quizzes, Mid-Semester Examinations (UTS), and UAS. Often, students have difficulty determining the minimum score they must obtain on the UAS to achieve an overall score sufficient to pass the course. This problem was overcome by developing an algorithm that utilizes value data that has been obtained from other assessment components to calculate the minimum value required on the UAS. This research also includes evaluating the effectiveness of the algorithm through a series of trials with different value data. Test results show that this algorithm provides accurate and reliable results. Apart from that, this algorithm is able to help students plan their study strategies better, because they can know with certainty the minimum score that must be achieved on the UAS to pass the course. Overall, this research makes a significant contribution to the field of education, especially in helping students understand and manage evaluations of their academic performance. It is hoped that this algorithm can be integrated into various learning tools and applications to maximize its benefits for students in various educational institutions.